1980
DOI: 10.1073/pnas.77.5.2551
|View full text |Cite
|
Sign up to set email alerts
|

Subclasses of external adenosine receptors.

Abstract: ABSTACT Cell surface adenosine receptors mediate either stimulation or inhibition of adenylate cyclase activity [ATP pyrophosphate-lyase (cyclizing), EC 4.6.1.1], and the receptors that mediate these different responses can be discriminated with selected adenosine analogs. 5'-N-Ethylcarboxamideadenosine is a more potent agonist at stimulatory receptors (Ra) than is N8-phenylisopropyladenosine, whereas the reverse potency order is seen with inhibitory receptors (Ri). The potency of adenosine is intermediate b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
445
3
8

Year Published

1981
1981
1999
1999

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 902 publications
(483 citation statements)
references
References 22 publications
27
445
3
8
Order By: Relevance
“…All the adenosine derivatives tested enhanced Ca2+-induced release of arachidonic acid in the order of potency PIA = CHA > CADO = NECA. This rank order is in accordance with that of agonist potencies for the A1 receptor [23]. The results were practically the same as those obtained in the ionomycin-and thapsigargin-provoked events (results not shown).…”
Section: Role Of [Ca2+] Increase and Protein Kinase C Activation In supporting
confidence: 88%
“…All the adenosine derivatives tested enhanced Ca2+-induced release of arachidonic acid in the order of potency PIA = CHA > CADO = NECA. This rank order is in accordance with that of agonist potencies for the A1 receptor [23]. The results were practically the same as those obtained in the ionomycin-and thapsigargin-provoked events (results not shown).…”
Section: Role Of [Ca2+] Increase and Protein Kinase C Activation In supporting
confidence: 88%
“…Londos et al (1980) showed that the A2 receptors in the liver had a very high affinity for NECA, an affinity much higher than those in the adrenal or Leydig cells. A possible third adenosine receptor has been identified in rat fat cells (Garcia-Sainz and To mer, 1985) and also centrally DeLo renzo, 1985, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…It is liberated from nucleotide pools under conditions of net ATP catabolism and, as a paracrine signal, invokes an array of physiological responses that collectively serve to protect cells during metabolic stress and tissue injury (Arch and Newsholme, 1978; for recent overviews, see Bruns, 1991;Engler and Gruber, 1991). Most of these actions are mediated by specific membrane adenosine receptors (A, and A,) which are coupled to signal transduction pathways by guanine nucleotide regulatory proteins (Londos et al, 1978(Londos et al, , 1980Maenhaut et al, 1990;Libert et al, 1991).…”
Section: Introductionmentioning
confidence: 99%